2010
DOI: 10.22436/jmcs.001.04.16
|View full text |Cite
|
Sign up to set email alerts
|

PID Control Of DC Motor Using Particle Swarm Optimization (PSO) Algorithm

Abstract: Wide amplitude, DC motor's speed and their facile control cause its great application in industries. Generally the DC motors gain speed by armature voltage control or field control. The suggestion method in this paper is using PSO Algorithm for regulation parameter PID control of DC motors. The Algorithm PSO using by defining the fitness functions so that the minimum error and overshoot design is easy to implement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The best previously visited position of the ith particle is denoted as P = [p p …p ] . Defining ''g'' as the index of the best particle in the swarm, where the gth particle is the best, and let the superscripts denote the iteration number, then the swarm is manipulated according to the following two equations [26].…”
Section: Particle Swarm Optimization With Pidmentioning
confidence: 99%
See 2 more Smart Citations
“…The best previously visited position of the ith particle is denoted as P = [p p …p ] . Defining ''g'' as the index of the best particle in the swarm, where the gth particle is the best, and let the superscripts denote the iteration number, then the swarm is manipulated according to the following two equations [26].…”
Section: Particle Swarm Optimization With Pidmentioning
confidence: 99%
“…Thought V has been found not to be necessary in the PSO with inertia version, however it can be useful and is suggested that a V =X be used [23][24][25][26][27]. The original procedure for implementing PSO is as follows: Fig.…”
Section: Typicallymentioning
confidence: 99%
See 1 more Smart Citation
“…System control model: Because the DC motor provides the driving force for the automatic side door system of EMU, the DC motor optimizing control is the automatic side door control core. Aiming the performance requirements for the operation of the automatic side door and combining with the features of automatic side door, the optimal control model of automatic side door system is established (Moghaddas et al, 2010). DC motor rotation speed model: DC motor rotation speed n can be expressed as Eq.…”
Section: Photoelectric Encodermentioning
confidence: 99%
“…These animals include bees, ants, wasps, and find a behavioural algorithm from the habits or behaviour of these animals. This includes genetic algorithmic, huge bang-big crunch improvement, artificial bee colony, particle swarm optimization, bacterial foraging, and flower pollination [20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%